Comparing two corrective exercise approaches for body image and upper-quadrant posture in schoolgirls with hyperkyphosis - Samineh Mokhtaran; Hashem Piri; Rahman Sheikhhoseini; Mohammad Salsali (Scientific Reports)
Abstract Proper posture is essential for healthy living. Maintaining an ideal upright posture is one of the most critical indicators of the health of the musculoskeletal and movement systems. The current study compared the effectiveness of 6 weeks of NASM-based exercise training and eccentric-based exercise programs on body image and upper-quarter posture in schoolgirls with hyperkyphosis. In this randomized, controlled study, two intervention groups that received 6 weeks of NASM and eccentric-based exercise were compared with a control group that did nothing but continue their daily activities. For the purpose of conducting the experiment, 14 subjects were assigned to two groups (eccentric-based and control), and 12 subjects were assigned to the NASM group by using a simple blocked randomization method. The body esteem scale questionnaire was used to assess participants’ body image in the groups. Likewise, the photogrammetric technique and Kyphometer were used to gather data from all groups before and after six weeks of targeted corrective exercises. Differences in responses to workouts across groups were investigated using analysis of variance-covariance (ANCOVA) followed by post hoc Bonferroni tests. The results from the ANCOVA analysis indicated significant differences between the experimental and control groups regarding the effects of time*group on kyphosis (P < 0.001), shoulder angle (P < 0.001), and forward head posture (P < 0.001). Nonetheless, there was no significant difference between the considered groups regarding body image (P = 0.617). Based on the Bonferroni test, we found a significant difference between the control and eccentric-based groups for postural parameters measured during the study (P < 0.001). Similarly, both the control and NASM groups demonstrated significant differences for all variables(P < 0.001), except the body image. However, we could not find any statistical difference between the NASM training group and the eccentric-based exercise group concerning the upper quarter postural variables that were mentioned before. This study demonstrates that compared with a control group, schoolgirls with hyper-kyphosis who received a six-week intervention of eccentric-based and NASM- based exercises had significantly improved postural parameters but not body image. Despite these advantages, the improved kyphosis, shoulder angle, and forward head posture did not differ significantly between the NASM-based and eccentric-based exercise groups.